2007
DOI: 10.1093/nar/gkm259
|View full text |Cite
|
Sign up to set email alerts
|

WoLF PSORT: protein localization predictor

Abstract: WoLF PSORT is an extension of the PSORT II program for protein subcellular location prediction. WoLF PSORT converts protein amino acid sequences into numerical localization features; based on sorting signals, amino acid composition and functional motifs such as DNA-binding motifs. After conversion, a simple k-nearest neighbor classifier is used for prediction. Using html, the evidence for each prediction is shown in two ways: (i) a list of proteins of known localization with the most similar localization featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
2,405
1
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 3,185 publications
(2,452 citation statements)
references
References 15 publications
32
2,405
1
14
Order By: Relevance
“…It is generally known that subcellular localization of a protein probably provides significant clues to its function (Horton et al, 2007). As cytosolic proteins with pools of both a soluble and stable form or reversibly connected with components of the cytoskeleton or proteins, annexins mediate interactions between cell and extracellular matrix (Moss & Morgan., 2004).…”
Section: Prognostic Significance Of Annexin A1 Expression In Pamentioning
confidence: 99%
“…It is generally known that subcellular localization of a protein probably provides significant clues to its function (Horton et al, 2007). As cytosolic proteins with pools of both a soluble and stable form or reversibly connected with components of the cytoskeleton or proteins, annexins mediate interactions between cell and extracellular matrix (Moss & Morgan., 2004).…”
Section: Prognostic Significance Of Annexin A1 Expression In Pamentioning
confidence: 99%
“…Bioinformatics toolDescriptionWebsiteReferenceTrimmomaticA fast, multithreaded command line tool that can be used to trim and crop Illumina data as well as to remove adapters.http://www.usadellab.org/trimmomatic [80] STARAn algorithm for aligning high-throughput long and short RNA-seq data to a reference genome.http://code.google.com/p/rna-star [81] SignalPSoftware that predicts signal peptide cleavage sites in proteins from eukaryotes and prokaryotes.http://www.cbs.dtu.dk/services/SignalP [82] WoLF PSORTAn algorithm that predicts the subcellular localization sites of proteins based on their amino acid sequences. It makes predictions based on both known sorting signal motifs and some correlative sequence features such as amino acid content.www.wolfpsort.org [83] TargetPTool that predicts subcellular location of eukaryotic proteins.http://www.cbs.dtu.dk/services/TargetP [84]
10.1080/21505594.2018.1504560-F0002Figure 2.Coherent pipeline to identify putative effector proteins of Plasmodiophora brassicae . The pipeline assumes: (1) Researchers are starting with RNA-Seq reads from a host plant infected with P. brassicae ; (2) The draft genomes available for P. brassicae , other plasmodiophorids, oomycetes, and other plant pathogens are used; (3) Motifs mentioned in the review or structural similarities with previously described effector proteins were identified.
…”
Section: A Coherent Pipeline To Identify Effectorsmentioning
confidence: 99%
“…Subcellular localization prediction by WoLF PSORT II (www.wolf psort.org) revealed either a mitochondrial (DNJ-10, also reported 85 ) or cytosolic (DNJ-12, DNJ-19) localization. 86 In consequence, class A J-proteins are missing in the ER. It could be hypothesized whether the presence of the zinc-finger domain in class A proteins is responsible for its lack in the ER.…”
Section: Redox-regulation Of Chaperonesmentioning
confidence: 99%